INNOVATION POTENTIAL OF FAMILY BUSINESS IN THE SPHERE OF HOTEL BUSINESS - Kyurova, Vyara; Davidkova , Blagovesta (Revista Inclusiones, 2019)
This research paper presents the results of a survey of the innovation potential of family business in the sphere of hotel business in Bulgaria. The aim is to clarify the theoretical problems connected with the innovation potential and assess this potential of family business in Bulgaria. The assessment of innovation potential is based on the results of a independently made survey of innovation potential of family business in hotel sphere. The term “innovation potential” of business is defined. Theoretical aspects of innovation potential are discussed, as well as, some factors influencing this potential and the system of indicators for assessment. Based on questionnaire survey is outlined the assessment of representatives of family business in hotel sphere as regards their innovation potential.